Can the social dimension of time contribute to explain the public evaluation of political change? The case of European integration. (February 2023) - Malang, Thomas
According to social theorists of time, the way societies structure and value different aspects of time plays an important role in people's perception and evaluation of economic, political, and cultural change. I explore if two dimensions of social time—social acceleration and long-term orientation—have an effect on the public evaluation of the speed of European integration. Combining Eurobarometer data for 27 societies with measures for social acceleration and time horizons, the results show distinct patterns for the perception and preferences of European integration. Whereas I find no connection between dimensions of social time and the perceived speed of integration, more social acceleration and cultural long-term orientation lead to a desire for a slower speed of European integration. Even when controlled for other economic and political macro-factors, temporal structures can play a key role in the evaluation of political change in European societies.